Italy’s Independent Urban Explorers - Andrea Mubi (lo Squaderno, 2012)
It is perhaps overstated to speak of an Italian renaissance of independent urban ethnography. Yet, the fact is that over the last decade we have seen young Italian fiction writers, photographers, film-makers, journalists, reporters and artists turn into urban explorers and veritable independent urban ethnographers. Certainly, in a country with a strong tradition of politicised art and counter-cultural production such as Italy, what counts as ‘independent’ always constitutes a sensitive topic and matter of heated debates, especially in relation to those who, for various reasons, come to be marked by the infamous label of ‘sell-outs’.